How do you multiply #(y+4) (3y^4 -2y^2 +1)#?

1 Answer
Aug 4, 2015

Answer:

#=color(blue)(3y^5 + 12y^4 −2y^3 −8y^2 + y + 4#

Explanation:

#color(blue)((y+4))(3y^4−2y^2+1)#

Here each term within the first bracket needs to be multiplied with all three terms of the second bracket.

#color(blue)((y)) * (3y^4−2y^2+1)+color(blue)(4) * (3y^4−2y^2+1)#

#=color(blue)((y)) * (3y^4−2y^2+1)+color(blue)(4) * (3y^4−2y^2+1)#

#=(3y^4*y−2y^2 * y +1*y)+ (3y^4*4 −2y^2*4+1*4)#

#=(3y^5−2y^3 +y)+ (12y^4 −8y^2+4)#

#=color(blue)(3y^5 + 12y^4 −2y^3 −8y^2 + y + 4#